Hypertensive phenotype signs in men with different genetic polymorphisms of aldosterone synthase and angiotensin II type 1 receptors - Susanna A. Tykhonova; Veronika P. Piskovatska (Kazimierz Wielki University, 2015)
Tykhonova Susanna, Piskovatska Veronika. Ознаки гіпертензивного фенотипу у чоловіків із різними поліморфними алельними варіантами генів альдостеронової синтази та рецепторів до ангіотензину ІІ 1 типу = Hypertensive phenotype signs in men with different genetic polymorphisms of aldosterone synthase and angiotensin II type 1 receptors. Journal of Education, Health and Sport. 2015;5(6):123-130. ISSN 2391-8306. DOI 10.5281/zenodo.18398 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A123-130 https://pbn.nauka.gov.pl/works/564165 http://dx.doi.org/10.5281/zenodo.18398 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 05.06.2015.   УДК 575.191:(616.12-008.331.1 +616.12-007.61)   ОЗНАКИ ГІПЕРТЕНЗИВНОГО ФЕНОТИПУ У ЧОЛОВІКІВ ІЗ РІЗНИМИ ПОЛІМОРФНИМИ АЛЕЛЬНИМИ ВАРІАНТАМИ ГЕНІВ АЛЬДОСТЕРОНОВОЇ СИНТАЗИ ТА РЕЦЕПТОРІВ ДО АНГІОТЕНЗИНУ ІІ 1 ТИПУ HYPERTENSIVE PHENOTYPE SIGNS IN MEN WITH DIFFERENT GENETIC POLYMORPHISMS OF ALDOSTERONE SYNTHASE AND ANGIOTENSIN II TYPE 1 RECEPTORS   С. А. Тихонова, В. П. Пісковацька Susanna Tykhonova, Veronika Piskovatska   Одеський національний  медичний університет Odessa National Medical University   Abstract. Single-nucleotide polymorphisms of renin-angiotensin-aldosterone system are widely discussed as the predictors of arterial hypertension, hypertensive target-organ damage, and antihypertensive treatment response. Controversies exist in numerous studies and meta-analyses of potential aldosterone synthase and angiotensin II type 1 receptors polymorphisms genes' role in hypertension onset and target-organ damage progression. Current study aimed to evaluate relative risk of blood pressure elevation and left ventricle hypertensive remodeling in young men with various CYP11B2 and AGT1R polymorphic variants. Odds-ratio analysis showed that high blood pressure and hypertension were diagnosed in CYP11B2 C244T T-allele carriers, with the highest relative risk in T-homozygous patients, as compared to CC-variant. C-allelic variants of AGT1R A1166C were associated with elevated blood pressure levels, while A-allele was linked to left ventricle hypertrophy. 5 times higher left ventricle hypertrophy was also observed in TT CYP11B2 C244T males, comparing to C-homozygous men. Keywords: hypertension, genetic predisposition, SNP, CYP11B2 C244, AGT1R A1166C.   Резюме. Мононуклеотидні поліморфізми генів ренін-ангіотензин-альдостеронової системи розглядаються в якості предикторів виникнення артеріальної гіпертензії (АГ), особливостей її перебігу та також відповіді на антигіпертензивну терапію. Суперечливі дані, нерідко в межах однієї етнічної групи, існують щодо патогенетичної ролі поліморфізмів-кандидатів компонентів РААС у виникненні та прогресуванні АГ та ураження-органів мішеней. Метою дослідження було визначення відносного ризику підвищення артеріального тиску (АТ) та гіпертрофії лівого шлуночка (ГЛШ) у молодих чоловіків із різними поліморфними алелльними варіантами генів CYP11B2 та AGT1R. Дані обстеження 80 чоловіків віком від 18 до 35 років демонструють збільшення відносного шансу підвищення АТ до високого нормального рівня та діагностування АГ у носіїв Т-алелю поліморфізму 344 С/Т CYP11B2. Відносний шанс наявності ГЛШ у монозиготних за Т-алеллю чоловіків був у 5 разів вищим за С-монозиготних осіб. Носійство та монозиготність за С-алеллю AGT1R A1166C асоціювалися із підвищеним рівнем АТ, в той час як носії АА та АС варіантів генотипу AGT1R частіше мали ГЛШ. Ключові слова: артеріальна гіпертензія, генетична схильність, мононуклеотидні поліморфізми генів, ген альостеронової синтази CYP11B2, ген рецепторів до ангіотензину ІІ 1 типу AGT1R.